Distal Decompression Beyond the Obersteiner-Redlich Zone Results in Similar Pain Outcomes Compared to Proximal Decompression in Endoscopic Microvascular Decompression for Trigeminal Neuralgia. (16th November 2020) - Blue, Rachel; Yang, Andrew; Saylany, Anissa; Spadola, Michael; Kvint, Svetlana; Harber, Alexander; Lee, John Y.K
Abstract: INTRODUCTION: Neurovascular decompression at the root entry zone (REZ) is the neurosurgical standard of care for trigeminal neuralgia (TN), but since the introduction of the endoscope the surgeon can identify distal vascular compression at the entrance into Meckel's cave even when conventionally hidden by the petrous tubercle. We hypothesized that distal decompression (especially venous) would yield inferior pain outcomes as compared to conventional arterial proximal brainstem decompression in patients with TN. METHODS: A six-year review of operative videos, charts and pain outcomes of 221 patients undergoing E-MVD for TN. The trigeminal nerve was visualized from pons to meckel's cave, and divided into half. Vascular compression was categorized as proximal (between pons to midpoint), distal (between midpoint to meckle's cave), or both (distinct areas of proximal and distal compression). Patients completed a questionnaire including a validated multidimensional pain-outcome tool, the Penn Facial Pain Scale (PFPS). RESULTS: Compression was found to be proximal in 137/221 (62%), distal in 36/221 (16.2%) and both in 48/221 (21.7%) of patients. There was no significant difference in pre or post-operative pain scores. SCA was the source of compression in 62.8% of proximal, 68.8% of both, and in 41.7% of distal ( P = .033). Venous compression was found in 69.4% of distal, 83.3% of both, and in 51.1% of proximal ( P < .001). There was no significant difference in complications. Of note, neurolysis was performed in 27.8% of distal compression, 19.7% with proximal compression and 6.3% with both. At last follow-up, pain was rated as "very much improved" or "much improved" in 87.9% of patients with proximal compression, in 92.9% with distal and in 89.5% with both ( P = .89). CONCLUSION: Proximal compression was most often associated with SCA; distal compression was most often venous. Regardless of location, patients did well following decompression. This finding could be, in part, due to the higher rate of neurolysis performed with distal compression. This study obviates the need to look for compression not only at the REZ, but distally as well. Neurolysis should be considered with distal-only compression.